The Oncogenic Effects, Pathways, and Target Molecules of JC Polyoma Virus T Antigen in Cancer Cells - Zheng, Hua-Chuan; Xue, Hang; Jin, Yu-Zi; Jiang, Hua-Mao; Cui, Zheng-Guo (Frontiers in Oncology, 2022)
JC virus (JCV) is a ubiquitous polyoma virus, and infects the individual to result in progressive multifocal leukoencephalopathy and malignancies. Here, we found that T antigen knockdown suppressed proliferation, glycolysis, mitochondrial respiration, migration, and invasion, and induced apoptosis and G2 arrest, while the converse was true for T antigen overexpression with the hyperexpression of Akt, survivin, Rb, β-catenin, β-TCRP, and ING1, and the hypoexpression of mTOR, p-mTOR, p-p38, Cyclin D1, p21, VEGF, ING2 and ING4 in hepatocellular and pancreatic cancer cells and tissues. In lens tumor cells, T antigen transcriptionally targeted viral carcinogenesis, microRNAs in cancer, focal adhesion, p53, PI3K-Akt, Foxo and Wnt signal pathway, ECM-receptor interaction, choline and pyrimidine metabolism. At metabolomics level, it did protein digestion and absorption, aminoacryl-tRNA biosynthesis, biosynthesis of amino acids, Foxo, PI3K-Akt, AMPK and mTOR signal pathway, and pyrimidine metabolism. At proteomic level, it did protein digestion and absorption, aminoacryl-tRNA, and amino acid biosynthesis, cholinergic synapse, AMPK and mTOR signal pathway, pyrimidine metabolism, mTOR signal pathway, PI3K-Akt signal pathway, and Foxo signal pathway. In lens tumor cells, T antigen might interact with various keratins, ribosomal proteins, apolipoproteins, G proteins, ubiquitin-related proteins, RPL19, β-catenin, β-Trcp, p53, and C/EBP in lens tumor cells. T antigen made the phenotypes of mouse and human cancer cells more aggressive by oncogene activation, inactivation of tumor suppressors, and disruption of metabolism, cell adhesion, and lncRNA-miRNA-target axes.